The Team Accelerated Instruction Model Improves Mathematics Learning Outcomes - Gunadewa S, M Berlianta; Japa, I Gusti Ngurah (Universitas Pendidikan Ganesha, 2022)
Teacher learning activities are less creative and innovative, especially in learning mathematics. Teachers also very rarely give assignments. Teachers do not apply innovative models, and teachers do not motivate students to learn. The interviews showed that the low learning outcomes of mathematics in students were due to the difficulty of developing students' understanding when studying. The purpose of this study is to analyze the effect of the TAI model on mathematics learning outcomes. This type of research is quasi-experimental. The total population is 125. The number of samples is 82. The data collection method is a test. The instrument that collects data is the question sheet. The data analysis techniques are descriptive and inferential statistics. The study's t-test analysis results obtained a significance value (2-tailed) of 0.000. Thus, it can be interpreted that there is a significant difference in mathematics learning outcomes following TAI learning with conventional learning. So, TAI can improve mathematics learning outcomes. This research implies that the application of TAI causes students' mathematics learning outcomes to increase. Students are enthusiastic and active during the learning activities.